A SEARCH FOR ENDOGENOUS AMINO ACIDS IN THE MARTIAN METEORITE EETA 79001 - McDonald G.D.; Bada J.L. (My University, 1995)
The Antarctic shergottite EETA 79001 is believed to be an impact-ejected fragment of the planet Mars. Samples of the carbonate (white druse) and the basaltic (lithology A) components from this meteorite have been found to contain amino acids at a level of approximately 1 ppm and 0.4 ppm, respectively. The detected amino acids consist almost exclusively of the L-enantiomers of the amino acids commonly found in proteins, and are thus terrestrial contaminants. There is no indication of the presence of α-aminoisobutyric acid, one of the most abundant amino acids in several carbonaceous chondrites. The relative abundances of amino acids in the druse material resemble those in Antarctic ice, suggesting that the source of the amino acids may be ice meltwater. The level of amino acids in EETA79001 druse is not by itself sufficient to account for the 600-700 ppm of volatile C reported in druse samples and suggested to be from endogenous martian organic material. However, estimates of total terrestrial organic C present in the druse material based on our amino acid analyses and the organic C content of polar ice can account for most of the reported putative organic C in EETA79001 druse.